PENGARUH PENGGUNAAN MEDIA RODA PINTAR TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SD BINA KASIH KECAMATAN PANAKKUKANG KOTA MAKASSAR - Rosdiah Salam; Widya Karmila Sari Achmad; Indahwati Mangedong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research analyzes the effect of using smart wheel media on the beginning reading skills of first-grade students at SD Bina Kasih, Panakkukang District, Makassar City. The study aims to describe the use of smart wheel media on first-grade students' beginning reading skills, to describe their beginning reading skills before and after the implementation of smart wheel media, and to determine the effect of using smart wheel media on the beginning reading skills of first-grade students. This study employed a quantitative approach with an experimental research design in the form of a Pre-Experimental Design with a One-Group Pretest-Posttest Design type. The sample used in this research was first-grade students at SD Bina Kasih, Panakkukang District, Makassar City. The data collection techniques employed in this study were observation and tests. For data analysis, both descriptive statistical analysis and inferential statistical analysis were used, with the aid of IBM SPSS Statistics Version 30. The results of this study indicate that the description of using smart wheel media on first-grade students' beginning reading skills falls into the very good category. Similarly, the description of first-grade students' beginning reading skills is also in the very good category. Furthermore, there is a proven significant positive effect of using smart wheel media on the beginning reading skills of first-grade students, as demonstrated by hypothesis testing using the t-test formula with the aid of IBM SPSS Statistics version 30.)